Proceedings of the 2003 Conference on Universal Usability - CUU '03 2003
DOI: 10.1145/957226.957227
|View full text |Cite
|
Sign up to set email alerts
|

Making chalk and talk accessible

Abstract: This paper investigates the development of an authoring package designed to mimic traditional "chalk and talk" delivery of content in education. It emphasizes the twin goals of making the output more accessible both for those with disabilities and for distance learners and also making the package usable by academic staff without requiring extensive training. It deals with issues arising from the capture of the material, the compromises and conflicts which are made in the satisfaction of accessibility guideline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It was also observed that lecturers' ASR accuracy rates were lower in classes compared with those achieved in the office environment. This has also been noted elsewhere (Bennett et al, 2002). Informal investigations have suggested this might be because the rate of delivery varied more in a live classroom situation than in the office, resulting in the ends of words being run into the start of subsequent words.…”
Section: Accuracymentioning
confidence: 55%
“…It was also observed that lecturers' ASR accuracy rates were lower in classes compared with those achieved in the office environment. This has also been noted elsewhere (Bennett et al, 2002). Informal investigations have suggested this might be because the rate of delivery varied more in a live classroom situation than in the office, resulting in the ends of words being run into the start of subsequent words.…”
Section: Accuracymentioning
confidence: 55%
“…Many recommendations for the design of accessible eLearning contents have been delivered by international standard organizations, as well as private educational initiatives worldwide [6] [7][8] [12]. However, their level of abstraction as well as their quantity, can make it very hard for educators, who might not have prior expertise on accessibility, to effectively incorporate them into their everyday authoring practices [9]. Also, compliance of a specific web content to guidelines, as it might be assessed by the most commonly used accessibility checkers, like Bobbly [3], Lift [4], A-Prompt [5] etc., is not sufficient for eLearning material, since these tools mainly perform a syntactic assessment of web pages, but say nothing about the adequacy of any equivalent-alternative contents created, to enable effective access to this materials by disabled users during learning.…”
Section: Methodological Approachmentioning
confidence: 99%
“…SSTAT utilises Nuance NaturallySpeaking for the speech recognition component, one of the generalpurpose speech-to-text applications. NaturallySpeaking can achieve impressive accuracy rates by trained speakers in controlled (Bennett et al, 2003). Users are required to carry out a brief initial training procedure to allow the software to get used to their voice, speech pace and accent.…”
Section: A Pragmatic Approach To Accurate Transcriptionmentioning
confidence: 99%